Pentingnya Penerapan Pendidikan Karakter Dalam Pembelajaran - Alwazir Abdusshomad (STAI Asy-Syukriyyah, 2018)
Character education is a system that instill character values in the students, which contains the components of knowledge, individual awareness, determination and the willingness and action to implement the values, both of the one God, yourself, fellow human beings, the environment, and nation, so that will materialize perfect man. This is consistent with the educational objectives set out in the Basic Law No. 20 of 2003 which states that: